Influences of fermentation conditions on the biosynthesy capacite of antibiotics against Fusarium oxysporum of two Streptomyces strains Streptomyces cyaneogriceus HD54 and Streptomyces hygroscopicus HD58 - Thanh Xuan, Le Thi; Chinh, Tang Thi (Academia Journal of Biology, 2014)
Two strains Streptomyces cyaneogriceus HD54 and S. hygroscopicus HD58 were isolated from soil samples in Vietnam. They produced antibiotic against the fungus F. oxysporum Fo47. These strains were mesophilic microorganisms and their growth temperature were about 25oC-37oC. The optimum temperature for their growth and their antibiotic biosynthesy was 30oC in the media with pH = 7. The medium A-12 was suitable for their growth and their antibiotic biosynthesy, with incubation temperature at 30oC and shaker rate of 220 rpm/min. The A-12 medium contained soluble starch, soybean powder, molasses, K2HPO4, CaCO3 and NaCl. These two strains HD54 and HD58 obtained maximum biomass at among 96h cultivation time. They started to biosynthesize antibiotic after 48h of incubation and obtained maximum antibiotic activity against fungus F. oxysporum Fo47 after among 120h of incubation. Their antibiotic activity was obtained only inner their mycelium and non-extracted in the liquid medium.